2020
DOI: 10.1101/2020.07.31.20166041
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Serological SARS-CoV-2 Lateral Flow Assays for Rapid Point of Care Testing

Abstract: Background. Rapid point-of-care tests (POCTs) for SARS-CoV-2-specific antibodies vary in performance. A critical need exists to perform head-to-head comparison of these assays. Methods. Performance of fifteen different lateral flow POCTs for the detection of SARS-CoV-2-specific antibodies was performed on a well characterized set of 100 samples. Of these, 40 samples from known SARS-CoV-2-infected, convalescent individuals (average of 45 days post symptom onset) were used to assess sensitivity. Sixty samples f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 25 publications
(28 reference statements)
0
22
0
Order By: Relevance
“…Finally, we characterized cross-reactive T cell responses in just 1 unexposed HD, because HD9 was the only unexposed HD in our cohort with preexisting immunity to SARS-CoV-2. Although we screened this individual using 2 different SARS-CoV-2 antibody tests with stated sensitivities of 100% among hospitalized patients by 3 weeks after symptom onset (24,25), negative findings do not definitively prove that this individual did not have asymptomatic infection. This is important, given the studies showing that seronegative exposed individuals can have SARS-specific T cell responses (7,26), although the cross-reactivity we describe here may also explain those results.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, we characterized cross-reactive T cell responses in just 1 unexposed HD, because HD9 was the only unexposed HD in our cohort with preexisting immunity to SARS-CoV-2. Although we screened this individual using 2 different SARS-CoV-2 antibody tests with stated sensitivities of 100% among hospitalized patients by 3 weeks after symptom onset (24,25), negative findings do not definitively prove that this individual did not have asymptomatic infection. This is important, given the studies showing that seronegative exposed individuals can have SARS-specific T cell responses (7,26), although the cross-reactivity we describe here may also explain those results.…”
Section: Discussionmentioning
confidence: 98%
“…Drawbacks of LFAs include their higher cost-per-test rate, their inability to analyze multiple samples simultaneously, their general lack of quantitative data, and importantly, a several-fold reduced sensitivity when compared to non-rapid testing methods (71,72). Although RDTs are theoretically ideal for POC usage, recent studies have demonstrated that many newly developed RDTs for SARS-CoV-2 have failed to meet the necessary standards for sensitivity and specificity when compared to non-rapid testing (71)(72)(73)(74)(75)(76). Therefore, for research purposes, LFAs are not the ideal choice.…”
Section: Testing For Sars-cov-2 Antibodiesmentioning
confidence: 99%
“…The characteristics of the study population and associated clinical specimens have previously been described. 8,12 In brief, the convalescent SARS-CoV-2 samples had been collected from COVID-19 patients who were confirmed positive by reverse transcription polymerase chain reaction (RT-PCR) at least 28 days prior to specimen collection (mean 45 days, SD 7.5). The pre-pandemic control samples were collected from a prior study of patients who presented to the Johns Hopkins Hospital Emergency Department with symptoms of an acute respiratory tract infection between January 2016 and June of 2019 as part of the Johns Hopkins Center for Influenza Research and Surveillance study.…”
Section: Clinical Specimens Testsmentioning
confidence: 99%
“…CoronaChek SARS-CoV-2 lateral flow assay and the Euroimmun IgG Spike ELISA were performed in accordance with the manufacturers' instructions and tests results previously reported on a different study on the same specimens. 8,12,13 Neutralizing antibody assay (titer and AUC determination) data were made available; their acquisition has previously been described. 12,14 Statistical Analyses Sensitivity of the assays was calculated among COVID-19 convalescent individuals and specificity was calculated among pre-pandemic population.…”
Section: Serological Assay Testing Using Commercial Assaysmentioning
confidence: 99%
See 1 more Smart Citation